Nanocurcumin Modulates Ultramicroscopic Changes in the β-Cells of Pancreas in Diabetic Mice - Potphode N. D; Daunde J. A; Nimbalkar M. S; Chandrasekhar Sagar B. K; Walvekar M. V. (International Journal of Pharma and Bio Sciences, 2021)
Nanotechnology is the advanced branch of science which has been implemented in agriculture, food and medical science and its related products. Nanoparticles represent a promising drug delivery system of controlled and targeted release. Though curcumin has many beneficial effects against health problems, it has limited use due to its poor bioavailability as concluded by a number of its pharmacokinetic studies. Also it is less soluble in water due to hydrophobic nature. These problems have been overcome by nanoformulation of curcumin. The present investigation aims to study the ultramicroscopic changes in β-cells of pancreas in alloxan induced diabetic mice (Mus musculus) after the administration of nanocurcumin (NC). NC is prepared by double emulsion evaporation method. Mice were divided into four groups viz, a) Control group (GI) b) Diabetic group (GII) c) Recovery group I- Curcumin (GIII) and d) Recovery group II- Nanocurcumin (GIV). Diabetic mice were treated with curcumin as well as NC at a dose of 150 mg/kg body weight intraperitoneally. Ultramicroscopic observations of β-cells of Islets of GII shows pyknotic nuclei and decrease in number of secretory granules of insulin as compare to GI . After treatment of curcumin and NC to GIII and GIV respectively, improvement in structure of nuclei of β-cells was observed and cytoplasm of β-cells filled with insulin granules of different sizes. Especially in GIV the secretion of insulin granules was increased significantly as compared to GII and GIII. It indicated that NC showed good bioavailability of curcumin along with increased insulin secretion by β-cells of Islets. Thus these results proved that NC modulates ultramicroscopic changes.